2013
DOI: 10.1080/13504622.2013.833594
|View full text |Cite
|
Sign up to set email alerts
|

Measuring student teachers’ understandings and self-awareness of sustainability

Abstract: Understanding sustainability is important, as people need to cope with issues associated with over-population and over-consumption. Education is seen as a key strategy to assist with the development of people's understandings of this complex concept, which could then lead to them being able to make more sustainable lifestyle decisions. In order to teach this concept, teachers need to understand sustainability. This paper investigated 77 New Zealand student teachers' understandings of sustainability and the lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
1
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 26 publications
(41 reference statements)
4
47
1
4
Order By: Relevance
“…This limited knowledge affected their self-efficacy to engage in critical discourse about sustainability, consistent with the findings of Effeney and Davis' (2013) study. However, they showed metacognitive capacity that is beyond the recognition of teachers in other research (Birdsall, 2014), perhaps indicating a move towards growing awareness due to the implementation and expectations of the Australian Curriculum (ACARA, 2011).…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…This limited knowledge affected their self-efficacy to engage in critical discourse about sustainability, consistent with the findings of Effeney and Davis' (2013) study. However, they showed metacognitive capacity that is beyond the recognition of teachers in other research (Birdsall, 2014), perhaps indicating a move towards growing awareness due to the implementation and expectations of the Australian Curriculum (ACARA, 2011).…”
Section: Discussionmentioning
confidence: 95%
“…The researchers maintain that if WA Graduate Diploma of Education pre-service primary teachers are not critically supported by appropriate sustainability pedagogical content knowledge at the pre-service level, or as part of an ongoing professional development program, sustainability as a cross curriculum priority in the Australian Curriculum (ACARA, 2011) could become marginalised (Birdsall, 2014). In addition, it is suggested that the personal perceptions of sustainability that pre-service primary teachers hold will shape the way they interpret sustainability as a cross-curriculum priority.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, there is a big gap in understanding between non-practitioners and sustainability practitioners (Birdsall, 2014;Garbie, 2015). According to L4, it is difficult to convince the academic staff members who are not in sustainabilityrelated disciplines to accept sustainability, because they perceive sustainability as irrelevant to their discipline.…”
Section: Sustainability Acceptance Is Influenced By Disciplinementioning
confidence: 99%